Associations Between DGAT1/Alu1 Gene Polymorphismand Some Performance in Morkaraman andTushin Sheep - Kopuzlu, S; Aydın, İ; Sönmez, Z; Ünal, H; Türkyılmaz, D; Türkyılmaz, Ü (Journal of the Hellenic Veterinary Medical Society, 2024)
DGAT is a microsomal enzyme that plays a central role in the biosynthesis of cellular triacylglycerols. The DGAT1 gene, which is involved in fatty acid metabolism, is accepted as a candidate gene for improving meat quality characteristics in sheep. In Morkaraman and Tuj sheep, The objective of the current research was to examine the genotypes of the myostatin gene and reveal the associations between the genotypes and some performance traits such as birth weight, weaning weight, weaning age, average daily weight gain, and productivity. Genotypes were determined by the PCR-RFLP method using the Alu1 restriction enzyme, and the genotype frequencies of Morkaraman and Tushin sheep were found to be 50% and 53%; 38.7% and 38%; 11.3% and 9% for CC, CT, and TT in the DGAT1 locus, respectively. It was defined that the C and the T allele frequencies were determined as 69% and 31% for Morkaramans and 72% and 28% for Tuj sheep, respectively. It was observed that the distribution of the DGAT1 gene locus examined in both breed populations was in balance according to the HW genetic equilibrium test. The association analysis revealed no statistically significant impact of the DGAT1 gene polymorphism in exon 3 on birth weight, weaning weight, weaning age, productivity, and daily live weight gain (P>0.05). DGAT1 gene showed polymorphisms in Morkaraman and Tushin sheep and can be regarded as a genetic marker for both sheep breed selection according to the association analysis results.